An appraisal of golimumab in the treatment of severe, active nonradiographic axial spondyloarthritis - Paccou J; Flipo RM (Dove Medical Press, 2016)
Julien Paccou, René-Marc Flipo Department of Rheumatology, Lille University Hospital, Lille, France Abstract: Golimumab (Simponi®) is a fully human tumor necrosis factor α inhibitor (TNFi) antibody administered subcutaneously. In the European Union, golimumab is indicated for the treatment of adults with severe, active axial spondyloarthritis (axSpA), which includes both ankylosing spondylitis (AS) and nonradiographic axSpA (nr-axSpA). In the US, it is indicated for the treatment of adults with active AS only. This article reviews the efficacy and tolerability of golimumab in nr-axSpA patients compared to other TNFi agents (adalimumab, infliximab, etanercept, and certolizumab pegol). In one ongoing, well-designed controlled study (GO-AHEAD), data at 16 weeks showed that treatment with golimumab (50 mg every 4 weeks) was effective in improving the clinical signs and symptoms of disease in nr-axSpA patients. In addition, 16 weeks of treatment with golimumab reduced inflammation in the sacroiliac joints and spine in patients with nr-axSpA. Moreover, objective evidence of active inflammation at baseline, such as a positive magnetic resonance imaging scan and/or an elevated CRP level, was a good predictor of treatment response to golimumab. Golimumab was generally well tolerated in this study, with a tolerability profile consistent with that seen in previous clinical trials for other indications. Although additional long-term data are needed, current evidence indicates that golimumab is an effective option for the treatment of nr-axSpA. However, in the absence of comparative head-to-head trials, there is no recommended hierarchy for the first prescription of a TNFi agent for the treatment of either nr-axSpA or AS. Keywords: axial spondyloarthritis, nonradiographic axial spondyloarthritis, ankylosing spondylitis, golimumab, tumor necrosis factor α inhibitor, therapy